The Moderating Role Of Change Management And Leadership Turnover: A Study Of Performance Accountability In Local Goverment - Septilia Woro Anggini; Rosidi Rosidi; Wuryan Andayani (Jurnal Reviu Akuntansi dan Keuangan, 2021)
The purpose of this study is to provide empirical evidence of the effect of the goverment internal control system and transparency on performance accountability by considering change management and leadership turnover  as the moderating variable. This study was conducted on Local Goverment Organization (OPD) of Muara Enim Regency. The unit of analysis is 118 employees whose work are involved in the preparation of performance accountability. This study using Structural Equation Modelling (SEM) statistical techniques with SmartPLS 3. This study finds that goverment internal control system and transparency has positive influence on performance accountability. Furthermore showed that change management doesn’t moderated the relationship between goverment internal control system and transparency on performance accountability. Leadership turnover successfully moderated the relationship between goverment internal control system and performance accountability. However leadership turnover doesn’t moderated the relationship between transparency and performance accountability. The results of this study can be used as evaluation material for the local government of Muara Enim Regency in the implementation of internal control system and transparency to achieve accountability of government performance. In addition, by looking at the factors of change management and change of leadership can provide benefits to local governments in carrying out tasks and obligations.